2003
DOI: 10.1128/aac.47.2.518-523.2003
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Antibiotic Dosage as a Risk Factor for Selection of Penicillin-Resistant Streptococcus pneumoniae : In Vitro Kinetic Model

Abstract: Streptococcus pneumoniae is the most significant bacterial cause of community-acquired respiratory tract infections (23). During the last decade, the spread of penicillin nonsusceptible pneumococci with increased MICs has created clinically significant treatment problems, especially in infections against which therapeutic concentrations are difficult to achieve, such as meningitis (1,(15)(16)(17)(18)28). Clinical and animal studies indicate, however, that by optimizing the dosing regimen, it may still be possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Our analysis indicates that as long as the dose is high enough, even if there are preexisting populations with reduced susceptibility, antibiotics can retard their rate of ascent and densities and thereby the likelihood that these "resistant cells" will be transmitted. For Streptococcus pneumoniae infections, for instance, there is both in vitro and in vivo evidence to show that, by using higher doses, β-lactam antibiotics can be used to treat some infections containing populations of bacteria that are officially "nonsusceptible" to the drug (69)(70)(71). Of course, because of toxicity and other side effects, there are limits to the concentrations at which most antibiotics can be used.…”
Section: Nb 1 Amentioning
confidence: 99%
“…Our analysis indicates that as long as the dose is high enough, even if there are preexisting populations with reduced susceptibility, antibiotics can retard their rate of ascent and densities and thereby the likelihood that these "resistant cells" will be transmitted. For Streptococcus pneumoniae infections, for instance, there is both in vitro and in vivo evidence to show that, by using higher doses, β-lactam antibiotics can be used to treat some infections containing populations of bacteria that are officially "nonsusceptible" to the drug (69)(70)(71). Of course, because of toxicity and other side effects, there are limits to the concentrations at which most antibiotics can be used.…”
Section: Nb 1 Amentioning
confidence: 99%
“…Although the breakpoint for penicillin resistance for nonmeningeal isolates has recently been increased to 8 g/ml (6), highly penicillin-and cephalosporin-resistant pneumococci are still emerging (25,30), and the effectiveness of existing ␤-lactams in the treatment of such infections is unlikely to be successful, as determined on the basis of the pharmacokinetics and pharmacodynamics of existing agents (1,27,29). Ceftaroline is a novel parenteral cephalosporin with broad-spectrum in vitro antimicrobial activity against resistant gram-positive pathogens, including penicillin-resistant S. pneumoniae strains and methicillin-resistant Staphylococcus aureus strains (14,28), as well as common gram-negative organisms.…”
mentioning
confidence: 99%
“…A number of in vitro studies have examined the effect of different dosing regimens in order to suppress the resistant subpopulations (1,10,23,31,35). A study by Negri et al (31) revealed that low antibiotic concentrations can affect the selection of bacterial populations that show only small differences in susceptibility.…”
mentioning
confidence: 99%